On the dynamic characteristics of box-girder bridges under moving vehicles - Mohammed, Atalla; Nikraz, Hamid (Engineers Australia, 2010)
In this paper, a parametric study to investigate the dynamic behavior of box-girder bridges under moving vehicles is presented. A higher order finite strip formulation based on the auxiliary nodal line (ANL) technique is implemented for vibration analysis. The free vibration analysis has been performed using the subspace iteration method. The dynamic response of both stiffened plate and box-girder bridges under moving vehicles is investigated. The vehicle is idealized as a One-Dimensional Moving Mass (1DMM) with 2DOF. A parametric study is undertaken to investigate the effect of some parameters and variables on the dynamic behavior of the bridges. These parameters are span length, vehicle velocity, vehicle damping and bridge damping. The concept of (Critical Velocity) is introduced to define the velocity that causes the maximum bridge response, and the Dynamic Amplification Factor (DAF) is studied with relation to several other factors like vehicle velocity, bridge damping, vehicle damping and bridge span length.